Using web services to put metamorphosis on the web - Librelotto, Giovani Rubert (2007)
This paper describes the exposure on the Web of Metamorphosis main functionalities. This exposure will be accom- plished through an XML Web Service. Metamorphosis is a Semantic Web tool aiming at the automatic creation of knowledge views for heterogeneous data sources or information systems. Each view is characterized by an ontology that corresponds to a semantic network composed of concepts and relations that are built with data extracted from several data sources. There are several formal notations for knowledge representation; Topic Maps were chosen due to their advantages like: having a frozen syntax which enables the creation of tools like extractors and navigators; and being abstract enough to specify anything (everything can be represented as a topic and these topics can relate to each other). The knowledge views are the final result of Metamorphosis but this tool has four different stages. We intend to expose each one of these stages. This way the desired XML Web Service will have four different modes, offering the following functionalities: f1: TM-Builder - the user provides a data source specification, and the Service will return an extractor for that data source. f2: TM - the user provides a data source specification together with the data source, and the Service will give the user the extracted Topic Map. f3: WebSite - the user provides a data source specification together with the data source, and the Service will send back the Website. f4: Remote WebSite - the user provides a data source specification together with the data source, and the Service will give the user an access point (URL) to the Website that will be hosted by the server. In the paper we will give enough information to understand Metamorphosis and all the layers developed so far. The four exposed functionalities of Metamorphosis will be discussed in detail.